Pengaruh Konsentrasi Polimer HPMC Terhadap Waktu Disintegrasi Orally Dissolving Film (ODF): Tinjauan Literatur - Elyona Ganis Azka Safuha; Devi Ratnasari; Siti Kalila Ramadhani; Yanti Windasari (Jurnal Sehat Mandiri, 2026)
Orally Dissolving Film (ODF) is an oral dosage innovation that can dissolve rapidly in the oral cavity without the need for water, thereby improving patient comfort and compliance. One of the critical parameters in evaluating ODF is disintegration time, which is influenced by the type and concentration of the film-forming polymer. Hydroxypropyl Methylcellulose (HPMC) is the most commonly used polymer due to its hydrophilic nature and excellent film-forming ability. This review aims to analyze the effect of HPMC concentration on the disintegration time of ODF, as well as to examine the influence of different types and combinations of other polymers. The method used was a literature review with a PICO approach. Articles were searched through Google Scholar and PubMed databases using the keywords “Orally Dissolving Film,” “HPMC,” “polymer,” “disintegration time,” and “formulation,” covering publications from 2017 to 2025. Nine articles met the inclusion criteria and were analyzed. The review results show that an increase in HPMC concentration generally prolongs disintegration time due to the increased viscosity and density of the film. However, differences in HPMC types (such as E5, E5 LV, and E15) and combinations with other polymers such as maltodextrin, PVA, and corn starch can enhance water absorption and accelerate disintegration time. Conclusion : The concentration and type of HPMC polymer affect the disintegration time of Orally Dissolving Film (ODF). Proper selection of polymer concentration and combination is necessary to achieve optimal disintegration time.